A Flexible Metal-Organic Framework with 4-Connected Zr6 Nodes - Zhang, Yuanyuan; Zhang, Xuan; Lyu, Jiafei; Otake, Ken-Ichi; Wang, Xingjie; Redfern, Louis R; Malliakas, Christos D; Li, Zhanyong; Islamoglu, Timur; Wang, Bo; Farha, Omar K (Journal of the American Chemical Society, 2018)
Zr-based metal-organic frameworks (MOFs) have been known for their excellent stability; however, due to the high connectivity of the Zr6 nodes, it is challenging to introduce flexibility into Zr-MOFs. Here we present a flexible Zr-MOF named NU-1400 comprising 4-connected Zr6 nodes and tetratopic linkers. It exhibits guest-dependent structural flexibility with up to 48% contraction in the unit cell volume as evidenced by single-crystal X-ray diffraction studies. The expanded or contracted conformations of NU-1400 showed drastically different reactivity toward the hydrolysis of a nerve agent simulant owing to the size-selective effect toward the reactant.Zr-based metal-organic frameworks (MOFs) have been known for their excellent stability; however, due to the high connectivity of the Zr6 nodes, it is challenging to introduce flexibility into Zr-MOFs. Here we present a flexible Zr-MOF named NU-1400 comprising 4-connected Zr6 nodes and tetratopic linkers. It exhibits guest-dependent structural flexibility with up to 48% contraction in the unit cell volume as evidenced by single-crystal X-ray diffraction studies. The expanded or contracted conformations of NU-1400 showed drastically different reactivity toward the hydrolysis of a nerve agent simulant owing to the size-selective effect toward the reactant.